Exploring the effectiveness of existential guilt appeal: durable products - Lwin, Michael; Phau, Ian (European Marketing Academy, 2012)
The study explores the relationships between existential guilt appeal, attitude towards the brand, inferences of manipulative intent, and purchase intentions. Research in advertising predominantly explores existential guilt appeal in the charitable donation context (e.g. Hibbert et al., 2007). Thus empirical findings from other contexts are needed, for example, the effectiveness of existential guilt appeal in the luxury durable context is unclear. The findings show no significant relationship between existential guilt appeal and purchase intentions. It questions why advertisers are using existential guilt appeal in luxury product advertisements. Managerial implications and future directions radiating from the results are discussed.